Design, modelling and fabrication of railway track cleaning bot - Francis, Neil Rodrigues; M, Arun; A.P, Sudheer (Procedia computer science, 2018)
The Indian railways is growing at a healthy rate and the government is taking initiatives to become the third largest railway market in the next five years. However there exists a growing concern over the waste disposal and management system adopted, calling for an immediate solution. With a major section of our Indian Railways relying on manual scavenging as a current solution, advances in Robotics and Automation calls for a more robust and effective system design that could call an end to the unhygienic conditions the manual scavengers are subject to and also ensure a cleaner railway network. The proposed autonomous railway track cleaning bot makes use of specially designed retractable wheels, an optimized height adjustable sweeper roller, chlorination unit, bot retracting mechanism and GPS-GSM module interfaced via AT commands. The problem was approached by kinematic and dynamic modelling along with the required static structural analysis of the bot. This paper is aims at provide a solution to the menace caused by littered waste taking into consideration the rail traffic that prevails along certain lines. This work would serve a cost effective yet time and life-saving solution to the existing problem.